A New Framework for IT Governance Excellence - Yulistiawan, Bambang Saras; Mulianingtyas, Rr Octanty; Widyastuti, Rifka; A , Galih Prakoso Rizky (International Journal of Enterprise Modelling, 2025)
The rapid digital transformation requires an organization to have adaptive, integrated governance and management of information technology services (IT). However, two popular frameworks, COBIT and ITIL, have weaknesses when implemented separately. COBIT seems too normative and strategic, while ITIL is too operational and procedural; therefore, both of them fail to align the requirements between the strategic direction and information technology service execution. This study proposes the CITIGOV Model, an integrative framework that aligns the strengths of COBIT and ITIL in a model of modular and adaptive governance and information technology service. With three main domains, Strategic Governance, Service-Oriented Management, and Continuous Value Optimization, and seven elements of sustainable operations in IT governance. This study employs the Design Science Research method and has been validated through a literature review, theoretical analysis, and the mapping of modern digital organisation needs. The result of this study not only delivers theoretical contributions to IT framework integration, but also the practical implications as well as relevant guidance implementation and applicability in the context of public or private organisations. Keywords: